Telework during the COVID-19 epidemic in Portugal and determinants of job satisfaction: a cross-sectional study - Mafalda Sousa-Uva; António Sousa-Uva; Marta Mello e Sampayo; Florentino Serranheira (BMC, 2021)
Abstract Background Telework satisfaction is a Public Health concern, intensified by the COVID-19 pandemic, and its determinant factors may be related with the negative health effects of teleworking. However, there is still little research exploring this issue. This study aimed to characterize telework during the first wave of the COVID-19 epidemic in Portugal and to identify the major predictors of telework satisfaction. Methods This is a cross-sectional study aimed at all teleworkers working in Portugal, during the first wave of the COVID-19 epidemic. Data were collected through a Google Forms platform online questionnaire distributed by a snowball method on social networks. Descriptive statistics included crude and relative frequency data. The associations between sociodemographic characteristics, self-perceived health, organization of working time, concentration at work, work-life balance, work disconnection, working conditions, and organizational demands (flexibility and organizational trust based on E-work Life Scale) with telework satisfaction were estimated through logistic regression. Results This study included 1004 participants. Teleworkers satisfaction levels were high (69%). Better concentration at work (OR = 1.54; 95%CI 1.01-2.34); the satisfaction with the balance between work life and extra work when teleworking (OR = 1.79; 95%CI 1.17-2.74); and higher work flexibility (OR = 2.26; 95%CI 1.46-3.49) were good predictors of greater levels of satisfaction with telework. However, its major predictors were the company's trust in teleworkers (OR = 4.50; 95%CI 2.89-7.02) and feeling good in the workspace at home (OR = 3.72; 95%CI 1.46-9.49). Conclusions Our findings point that work environment and organizational culture play a crucial role in affecting telework satisfaction. More studies are needed to monitor telework satisfaction and its effects on physical and mental health, so that Public and Occupational Health (and Safety) can be able to identify and implement the best interventions that allow promoting individual health and foster a healthy work environment for teleworkers.